Case Report: Trans-axillary Artery Access for Rescue Stent Implantation in an Infant With Retrograde Non-passable Aortic Coarctation - Moosmann, Julia; Purbojo, Ariawan; Eder, Susanne; Dittrich, Sven (Frontiers in Pediatrics, 2021)
Primary surgical repair remains the traditional treatment for patients with critical duct-dependent coarctation of the aorta (CoA). Initial surgical repair might not be possible or associated with higher risks if additional comorbidities arise in small infants and neonates. Balloon angioplasty (BA) has been described as a rescue strategy for these children. We describe the feasibility of a palliative BA and rescue stent implantation via an alternative antegrade right-axillary artery approach in an initially inoperable infant with pneumonia and respiratory failure and severe CoA, where the stenosis was not passable by traditional retrograde femoral access. This case adds new aspects to the therapy of critical CoA: Stent implantation provides a bridge to surgery in critically ill infants and does not preclude successful surgical repair. Further, if the classic retrograde approach is not possible, the right axillary artery access should be considered as an alternative to pass the stenosis.